Encouraging self-regulated learning through electronic portfolios - Philip C. Abrami; Anne Wade; Vanitha Pillay; Ofra Aslan; Eva M. Bures; Caitlin Bentley (The Canadian Network for Innovation in Education (CNIE), 2009)
At the Centre for the Study of Learning and Performance (CSLP) at Concordia University in Montreal, Quebec, we have developed the Electronic Portfolio Encouraging Active Reflective Learning Software (ePEARL) to promote student self-regulation and enhance student core competencies. This paper summarizes the literature on electronic portfolios (EPs), describes ePEARL, and documents our research findings to date including analyses of teacher and student reactions. Participants in this study were 62 school teachers, mostly from elementary schools, and their students (approximately 1200) from seven urban and rural English school boards across Quebec. Student and teacher post-test questionnaire responses suggested that the use of portfolios, and the learning processes they support, were positively viewed and learned well enough to be emerging skills among students. Contrariwise, teachers commented that teaching SRL strategies was new and thus required a change in teaching strategies, strategies that they were not yet accustomed to. Focus groups also revealed the challenges of using portfolios to teach children to self-regulate. And finally, the analysis of student portfolios evidenced only small amounts of student work or high levels of student self-regulation. Résumé : Au Centre d'études sur l'apprentissage et la performance (CEAP) de l'Université Concordia à Montréal, Québec, nous avons conçu le logiciel de portfolio électronique réflexif pour l'apprentissage des élèves (PERLE) afin d'encourager l'apprentissage autorégulé chez les élèves et d'accroître leurs compétences de base. Cet article présente un résumé de la documentation sur les portfolios électroniques, une description de PERLE, ainsi que nos résultats de recherche documentés à ce jour, y compris des analyses des réponses des enseignants et des élèves. Les participants à cette étude se composaient de 62 enseignants, la plupart dans des écoles primaires, et de leurs élèves (environ 1200) provenant de sept commissions scolaires anglophones urbaines et rurales du Québec. Les réponses des élèves et des enseignants au posttest suggèrent que les portfolios et les processus d'apprentissage qu'ils soutiennent ont été perçus de manière positive et qu'ils ont été suffisamment assimilés pour se traduire par de nouvelles compétences chez les élèves. En revanche, les enseignants ont mentionné qu'enseigner les stratégies d'apprentissage autorégulé était nouveau et que cela exigeait de modifier leurs stratégies d'enseignement pour en adopter d'autres auxquelles ils n'étaient pas encore habitués. Les groupes de discussion ont également fait ressortir les défis liés à l'utilisation des portfolios dans le but d'apprendre l'autorégulation aux enfants. Enfin, l'analyse des portfolios des élèves a révélé que seulement une petite portion des travaux d'élèves démontrait des niveaux élevés d'autorégulation.